Habermas e Foucault: entre o universal e o particular: um debate ético filosófico da contemporaneidade - Bonin, Joel Cesar (2008)
This study aimed to examine the works of Michel Foucault and Jürgen Habermas, the views that each author has, on contemporary ethics. The two thinkers have points of reference and thought very different. Foucault addresses through the History of Sexuality and how a person can be as thinkers and protagonists of an ethics focused on subjectivity, directed to a personal care of themselves. His texts refer to greek life and the possibility of a life guided by an aesthetic of existence, where universal precepts don t have chance. Habermas, however, part of a different paradigm and almost antagonistic. He believes that the living world was colonised and was alienated by a systemic world, where money and the State are their most expressive bulwarks. The output for this colonization is, to Habermas, the communicative action, which by means of language, the person interact and seek through the use of rationality argumentative, the consensus. This exercise is rational, according Habermas, the most appropriated option for the balance between objectivity and subjectivity of the human beings in the world. Indeed, communication is an intersubjective action, which takes into account the inclusion of other, the acceptance of the argumentation of others and the intent of the search for harmonization between the private and public sphere. The problem of Habermas lies in his desire to make the communicative action a universal action, valid for all. Habermas, therefore, develop an ethical theory that regards any act of speech has a claim to validity. The act of saying has an intention, a purpose. If this act of speech is valid or not, will depend on the analysis of the community in which the man is posed to discuss, it will depend on the strength of the argument and the acquiescence of the better argument. This act of putting under discussion is what will validate or not the argument. According Habermas, what matters is that this discussion should be free from coercion or domination. Something that Foucault understand how impossible, as every speech itself has power. It is not something that can be discarded or forgotten. In other words, according Foucault, the speech itself is power, whoever speaks. With this, we can see that Habermas and Foucault have very different points of view on what it means to be ethical. This work, in the end, shows that Foucault attempts to show that taking care of themselves is a free opportunity to be ethical, where through personal techniques, the subject search to know and meet themselves, with their bodies and their sexuality as a focus of this process.